TAHFIDZ SCHOLARSHIP PROGRAM IN COACHING GENERATION OF THE QURAN (Service Program of Zakat Management Unit of Ibn Khaldun University Bogor) - Ibdalsyah, Ibdalsyah; Rahmat Rosyadi, Abdu; Alim, Akhmad; Taqwa, Hafiz (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The phenomenon of people who learn the Quran today is not limited to being able to read properly and correctly based on the science of Tajweed, but there is a tendency to memorize the Quran as Hafidz/Hafidzah in part or 30 juz al-Quran. The method of service for the scholarship program of the Union of Zakat Management of Ibn Khaldun University Bogor for hafid/hafidzhah al-Quran students as one of the community services carried out through four steps of activities starting from selection, determination, assignment, mentoring, and evaluation of memorization activities of the Quran as an effort to nurture generations of the Quran. Based on the results of coaching the hafidz/ hafidzah al-Quran, it is stated that students can consistently maintain mutqin 30 juz while carrying out lectures in the program study within the Faculty.